Pan-Cancer Survey of Tumor Mass Dormancy and Underlying Mutational Processes - Wiecek, Anna Julia; Jacobson, Daniel Hadar; Lason, Wojciech; Secrier, Maria (Frontiers in Cell and Developmental Biology, 2021)
Tumour mass dormancy is the key intermediate step between immune surveillance and cancer progression, yet due to its transitory nature it has been difficult to capture and characterise. Little is understood of its prevalence across cancer types and of the mutational background that may favour such a state. While this balance is finely tuned internally by the equilibrium between cell proliferation and cell death, the main external factors contributing to tumour mass dormancy are immunological and angiogenic. To understand the genomic and cellular context in which tumour mass dormancy may develop, we comprehensively profiled signals of immune and angiogenic dormancy in 9,631 cancers from the Cancer Genome Atlas and linked them to tumour mutagenesis. We find evidence for immunological and angiogenic dormancy-like signals in 16.5% of bulk sequenced tumours, with a frequency of up to 33% in certain tissues. Mutations in the CASP8 and HRAS oncogenes were positively selected in dormant tumours, suggesting an evolutionary pressure for controlling cell growth/apoptosis signals. By surveying the mutational damage patterns left in the genome by known cancer risk factors, we found that ageing-induced mutations were relatively depleted in these tumours, while patterns of smoking and defective base excision repair were linked with increased tumour mass dormancy. Furthermore, we identified a link between APOBEC mutagenesis and dormancy, which comes in conjunction with immune exhaustion and may partly depend on the expression of the angiogenesis regulator PLG as well as interferon and chemokine signals. Tumour mass dormancy also appeared to be impaired in hypoxic conditions in the majority of cancers. The microenvironment of dormant cancers was enriched in cytotoxic and regulatory T cells, as expected, but also in macrophages and showed a reduction in inflammatory Th17 signals. Finally, tumour mass dormancy was linked with improved patient survival outcomes. Our analysis sheds light into the complex interplay between dormancy, exhaustion, APOBEC activity and hypoxia, and sets directions for future mechanistic explorations.